Tributação oculta nos serviços públicos regulados: o custo social da regulação e a transparência fiscal - Carvalho, Ivo César Barreto de (2016)
A series of reforms promoted in the Brazilian state apparatus, in the 1990s, led to the development of a state model with a lower level of direct involvement in the economy, making room in the market for the exploitation of certain economic activities and public services before monopolized by de State in Brazil. With denationalizating and privatizing measures, from which it made concessions, delegations and permissions of public services, among other ways of providing these aforesaid services, regulatory agencies - state entities with autonomy and administrative, regulatory and judicial powers – were instituted with the powers to monitor and regulate the public services as well as to mediate conflicts between the Public Government, public service providers and users. Imbued with the obligation to maintain adequate, quality and efficient services, regulatory agencies in Brazil adopt different tariff models, based on regulatory governance, but without being able to predetermine an ideal regulatory model, given the various constitutional, legal, technical and economic tariff regulation parameters. Thus, the taxation of regulated utilities must be discussed, it should be detailed the legal tax regime of public services, taking into account the division of tax powers between federal entities. Set these assumptions, we study the phenomenon of "hidden or disguised taxation" in public services, comparing this expression with the tax legal definition in Brazilian legal system and thus identifying its configuration in some current compensation species present in Brazil public services, such as the granting value, overpricing in state monopolies and compulsory use services compensation. Finally, identified the problems of "hidden or disguised taxation" in regulated utilities, how regulation can be an instrument for achieving the fundamental objectives of Brazilian Republic should be investigated, as well as inducing instrument of public policy, and so how can a fair taxation of public services be achieved, thus ensuring the human dignity of the before mentioned services users. This pursuit of ideal taxation should be parameterized by values such as transparency, morality, efficiency, fiscal consciousness and fiscal citizenship